1995
DOI: 10.1038/ki.1995.18
|View full text |Cite
|
Sign up to set email alerts
|

Excess PTH in CRF induces pulmonary calcification, pulmonary hypertension and right ventricular hypertrophy

Abstract: Calcification of the lungs occurs in chronic renal failure (CRF) and may adversely affect both pulmonary and right ventricular function. The present study examined the role of excess parathyroid hormone (PTH) in the genesis of pulmonary calcifications in dogs with experimental CRF and evaluated calcium content of lungs, diffusing lung capacity (DCO), mean pulmonary artery pressure (MPAP), right ventricular pressure (RVP), and right ventricular hypertrophy (RVH) in six normal, six with CRF, and six thyroparathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
4

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 26 publications
2
50
4
Order By: Relevance
“…In uremic dogs, electroencephalogram slowing can be substantially reduced with parathyroidectomy either before the dogs are made uremic or after the presence of uremia, and infusing PTH into normal animals could reproduce these findings (26). Other animal data support that parathyroidectomy in uremic dogs could also improve glucose intolerance (27), and reverse increased pulmonary calcification and hypertension with right ventricular hypertrophy (28).…”
supporting
confidence: 51%
“…In uremic dogs, electroencephalogram slowing can be substantially reduced with parathyroidectomy either before the dogs are made uremic or after the presence of uremia, and infusing PTH into normal animals could reproduce these findings (26). Other animal data support that parathyroidectomy in uremic dogs could also improve glucose intolerance (27), and reverse increased pulmonary calcification and hypertension with right ventricular hypertrophy (28).…”
supporting
confidence: 51%
“…In concordance with our results, Mousavi et al 29 demonstrated an association between low serum albumin, hemoglobin levels, and PH in HD patients. As difference in hemoglobin levels was similar between patients with and without PH in our study, Akmal et al 30 proved that increased parathyroid hormone (PTH) levels in CKD could cause calcification of pulmonary artery and leading to PH. We could not detect a difference in parameters, PTH, calcium, phosphorus, Ca  P product and 25-OH vitamin D levels between patients having PH and normal PAP.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, CKD is associated with endothelial dysfunction, arterial stiffness, and elevated parathyroid hormone, factors implicated in the development of PH. [24][25][26][27] Our ability to identify the etiology of PH was limited in this large epidemiologic study. Hence, future mechanistic studies, possibly including right heart catheterization, may offer additional insights.…”
Section: Discussionmentioning
confidence: 99%